On constrained uniform approximation - M. A. Bokhari (International Journal of Mathematics and Mathematical Sciences)
The problem of uniform approximants subject to Hermite interpolatory constraints is considered with an alternate approach. The uniqueness and the convergence aspects of this problem are also discussed. Our approach is based on work of P. Kirchberger (1903) and a generalization of Weierstrass approximation theorem.